Depression, anxiety, and stress among college students: a Kashmir-based epidemiological study - Sudershan, Amrit; Rehman, Sumaira; Manzoor, Tafazul; Shaban, Basharat; Sultan, Seerat; Pushap, Agar Chander; Sudershan, Srishty; Bashir, Mehraj; Malik, Showkat Ahmad (Frontiers in Psychiatry, 2025)
IntroductionDepression and anxiety are major public health concerns, especially among young adults. However, limited regional data exist from Kashmir, Northern India, to guide targeted mental health strategies. Therefore, the present study aimed to assess the levels of depression and anxiety among college-going students in Kashmir and examine associated demographic factors. MethodsA cross-sectional survey was conducted from January to April 2024, involving 1,471 college students aged 18 to 26 years from institutions across the Kashmir division. Data were collected using an online Google Form after obtaining informed consent. Depression and anxiety were measured using validated scales: PHQ-9 and GAD-7. Statistical analyses included t-tests, chi-square tests, logistic regression, and Pearson correlation to explore associations and trends. ResultsAmong the participants, 12.5% exhibited severe depression, with a slightly higher prevalence in females (13.39%). Severe anxiety was reported by 24.26% of students, and 19.17% reported high perceived stress levels. Gender showed notable relevance with anxiety (OR ≈ 1.68, p = 0.0001) and stress (OR ≈ 1.65, p = 0.0007). Correlation analysis revealed positive relationships between depression and stress score (r = 0.6322), anxiety and stress score (r = 0.6824), and depression and anxiety (r = 0.8064), suggesting that higher stress levels correlate with increased depression and anxiety among surveyed individuals. DiscussionThe high prevalence of depression, anxiety, and stress among college students, especially among females, highlights an urgent need for gender-sensitive, campus-based mental health interventions. The strong interrelations among these psychological conditions suggest that comprehensive stress-reduction programs may effectively mitigate multiple mental health risks. Future research should focus on designing and evaluating such targeted strategies to enhance student well-being.